GE_GERICHTE C/2125/2013 vom 28. Juni 2013 - GE Cour de justice (2013)
MESURE PROVISIONNELLE; INSCRIPTION; REGISTRE DU COMMERCE; CONSEIL D'ADMINISTRATION; MEMBRE | CPC.317.1; CPC.261.1; CO.701.1; CO.689a.2; CO.88.1